Low-temperature absorption spectra and electron structure of HoFe3(BO3)4 single crystal - Malakhovskii, A.V.; Gnatchenko, S.L.; Kachur, I.S.; Piryatinskaya, V.G.; Gudim, I.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Polarized absorption spectra of HoFe3(BO3)4 single crystal in the range of 8500–24500 cm–1 were studied asa function of temperature beginning from 2 K. The ground and excited electron states of Ho3+ were identified.The abrupt changes of the spectra at the reorientation phase transition at 4.7 K were observed. The exchange splitting of some excited states were revealed and measured. They changed at the reorientation phase transition. Several vibronic transitions were observed. The splitting of absorption lines corresponding to the C2 local sym-metry of the Ho ion was not observed. Moreover, spectra of some absorption bands correspond to splitting in the cubic crystal field. There are some absorption lines, whose polarization can not be explained both in D3 and C2 local symmetries. Some lines appear or disappear as a result of the transition from the easy axis to the easy plane state of the crystal. All these observations testify to the substantial changes of the local magnetic and structural properties in the excited states of the Ho3+ ion and to the strong influence of the magnetic moments orientationon the polarization of the electron transitions.